Bisphenol A exposure during the embryonic period: Insights into dopamine relationship and behavioral disorders in Drosophila melanogaster. - Musachio, E.A.S.; de Freitas Couto, S.; Poetini, M.R.; Bortolotto, V.C.; Dahleh, M.M.M.; Janner, D.E.; Araujo, S.M.; Ramborger, B.P.; Rohers, R.; Guerra, G.P.; Prigol, M. (Food and Chemical Toxicology, 2021)
Environmental factors are involved in the pathogenesis of neurodevelopmental disorders in addition to genetic factors. In this sense, we demonstrated here that the embryonic exposure of Drosophila melanogaster to Bisphenol A (BPA) 1 mM resulted in changes in development, behavior, and biochemical markers punctuated below. BPA did not alter the oviposition and viability of the eggs, however, it was evidenced a decrease in the rate of pupal eclosion and life span of the hatched flies of the generation filial 1 (F1). F1 flies also developed behavioral changes such as incompatibility in the social interaction between them, and hyperactivity demonstrated by increased locomotion in open field tests, increased grooming, and aggression episodes. Furthermore, decreases in dopamine levels and tyrosine hydroxylase activity have also been observed in flies' heads, possibly related to oxidative damage. Through analyzes of oxidative stress biomarkers, carried out on samples of flies' heads, we observed an increase in malondialdehyde and reactive species, decrease in the activity of the superoxide dismutase and catalase, which possibly culminated in the reduction of cell viability. Thus, it is important to emphasize that BPA developed atypical behaviors in Drosophila melanogaster, reinforce the importance of the environmental factor in the development of neurobehavioral diseases.